Cd and Zn in Nerita lineata collected from selected areas of the southern west coast of Peninsular Malaysia - Yap, Chee Kong; Cheng, W. H.; Zakaria, Mohamad Pauzi; Aris, Ahmad Zaharin; Tan, Soon Guan (UMT Publisher, 2013)
The concentrations of Cd and Zn were determined in Nerita lineata snails and sediments collected from Johore and Klang between May 2010 and April 2011. This study found variations of heavy metal accumulations in the shells, opercula and soft tissues. The mean concentrations (μg/g dry weight) of Cd and Zn were 5.42 and 8.11 for shells; 5.60 and 14.26 for opercula; 3.08 and 110.90 for soft tissues, respectively. The mean concentrations (μg/g dry weight) of Cd and Zn for surface sediments were 1.76 and 88.78, respectively. Generally the results of this study were comparable with those of previous reports on the same species.